Credit risks and monetary policy within Caribbean economies - Rumile Arana; Francisco A. Ramirez; Allan Wright (Inter-American Development Bank (IDB), 2017)
Our paper addresses the issue on the interaction between monetary and macroprudential policies in small open economies for different exchange rate regimes. The need for macroprudential policy arises from exacerbated macroeconomic fluctuations due to frictions in the financial system as in Bernanke, Gertler and Gilchrist (1999). Understanding these dynamics in developing nations has been even more important after the most recent events of the Great Recession. Policy makers within the scrutinized economies will see the exact magnitude of shocks caused by changes in financial frictions, monetary and macroprudential policy. Exchange rate considerations are also brought to the fore, by assessing the effects of these policies on two emerging economies from the Caribbean with differing monetary policy frameworks. Despite differences between flexible and fear of floating exchange rate regimes, macroprudential policies implementation help mitigate the effects of credit supply shocks affecting regional economies.
hdl:11319/8268
Keywords: E42; E43; E52; 330; Monetary Policy; Macroprudential Policy; Interest Rates; Capital Controls and Flows; DSGE